Evaluation of agricultural products and by-products as animal feeds v. utilization of pineapple bran and stearin by chickens. - Hutagalung, R. I.; Chey, T.W.
An experiment involving broiler chickens was undertaken to evaluate the feeding values of several graded mixtures of pineapple bran (5,10,15%) and stearin (3,6 and 9%) supplementation in pelletted broiler diets. There was no appreciable difference in weight gain when the combined levels of pineapple bran and stearin in the diets were increased. Regardless of stearin level,increasing level of pineapple bran brought about poorer feed conversion,less fat deposition and higher moisture content of the carcass. Summed over pineapple bran level,increased stearin level supplementation in the diets improved feed efficiency,reduced moisture and increased fat content of the carcass. Incorporation of 5% pineapple bran and 9% stearin into the diet gave the best performance of the broiler chickens.